2014
DOI: 10.1371/journal.pone.0109628
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Statin on Epithelial-Mesenchymal Transition in Peritoneal Mesothelial Cells

Abstract: BackgroundStatins have recently been highlighted for their pleiotropic actions distinct from cholesterol-lowering effects. Despite this interest, it is currently unknown whether statin therapy inhibits peritoneal dialysis (PD)-related epithelial-mesenchymal transition (EMT).Methods In vitro, human peritoneal mesothelial cells (HPMCs) were exposed to 5.6 mM glucose (NG) or 100 mM glucose (HG) with or without simvastatin (1 µM). In vivo, PD catheters were inserted into 32 Sprague-Dawley rats, and saline (C, n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…The inhibitory effect of statins on peritoneal dialysis‐related epithelial‐mesenchymal transition in rats has been reported. It revealed that statins could reverse the EMT signature, such as low expression of E‐cadherin and high expression of a‐SMA, by the mevalonate pathway . It was also reported that simvastatin inhibits the EMT in TGF‐β1‐treated DU145 prostate cancer cells reducing N ‐cadherin and VIM expressions.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The inhibitory effect of statins on peritoneal dialysis‐related epithelial‐mesenchymal transition in rats has been reported. It revealed that statins could reverse the EMT signature, such as low expression of E‐cadherin and high expression of a‐SMA, by the mevalonate pathway . It was also reported that simvastatin inhibits the EMT in TGF‐β1‐treated DU145 prostate cancer cells reducing N ‐cadherin and VIM expressions.…”
Section: Resultsmentioning
confidence: 92%
“…It revealed that statins could reverse the EMT signature, such as low expression of E-cadherin and high expression of a-SMA, by the mevalonate pathway. 27 It was also reported that simvastatin inhibits the EMT in TGF-β1-treated DU145 prostate cancer cells reducing Ncadherin and VIM expressions. Moreover, it causes an increase in the E-cadherin expression.…”
Section: Breast Cancer Stem-like Cell Selection and Dose-response Smentioning
confidence: 94%
“…It will be necessary to select agents with EMT inhibitory effect for the primary lesion during preoperative treatment. It is well known that low-dose paclitaxel (41)(42)(43)(44), metformin (45)(46)(47), angiotensin receptor blocker (48,49), statins (50,51), and histone deacetylase inhibitors (52,53) have all been indicated as agents that can inhibit the EMT of tumor cells or activation of stromal cells. Many papers have focused on the inhibition of tumor EMT and CAFs activation with paclitaxel (44,54,55).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that MFG-E8 was implicated in regulating phagocytosis through its interaction with Crk-DOCK180-Rac1 pathway 19 . Rac1 aggregates at the cell membrane which promotes formation of protrusion, thus plays an essential role in phagocytosis 24 . In the present study, 10% CSE stimulation suppressed Rac1 membrane localization in RAW264.7 cells.…”
Section: Resultsmentioning
confidence: 99%